Analysis of The Translation of Psycholinguistic Features In Pride and Prejudice By Jane Austen - Tukhlieva Zahro; Isakova Nodira Azzamovna (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2026)
This article examines the translation of psycholinguistic features in Pride and Prejudice by Jane Austen. The research explores how cognitive processes, emotional subtleties, character idiolects, irony, and socio-pragmatic norms embedded in the original text are transferred into another language. Particular attention is paid to free indirect discourse, internal monologue, politeness strategies, gendered linguistic behavior, and Regency-era cultural conventions. Through qualitative textual analysis grounded in translation theory and psycholinguistics, the article identifies key challenges and evaluates strategies such as modulation, explicitation, stylistic compensation, and pragmatic adaptation. The findings demonstrate that translating Austen requires not only linguistic accuracy but also sensitivity to psychological depth and narrative voice.